2022
DOI: 10.3390/ijms23042159
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Effect of Acidic Mammalian Chitinase Inhibitor OAT-177 in DSS-Induced Mouse Model of Colitis

Abstract: Inflammatory bowel diseases (IBD) are chronic and relapsing gastrointestinal disorders, where a significant proportion of patients are unresponsive or lose response to traditional and currently used therapies. In the current study, we propose a new concept for anti-inflammatory treatment based on a selective acidic mammalian chitinase (AMCase) inhibitor. The functions of chitinases remain unclear, but they have been shown to be implicated in the pathology of various inflammatory disorders regarding the lung (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The presence of positively charged side chains in the binding pockets of both proteins plays a role in electrostatic interactions (Arg35 and Arg263 in CHI3L1 and Arg104 and Arg132 in CHIT1) further demonstrating shared evolutionary origin of their sugarbinding capabilities. 56 Building upon these structural insights, we hypothesized that it would be feasible to find small molecule binders of CHI3L1 among our library of potent chitinase inhibitors OATD-01, 57−59 OAT-177, 60,61 OAT-870, 62 OAT-1441, 63 OAT-2068, 64 and their close analogues. To validate this hypothesis, we employed a biophysical technique, microscale thermophoresis, to assess direct binding of approximately 500 compounds from our chitinase inhibitors library to fluorescently labeled CHI3L1 and mCHI3L1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of positively charged side chains in the binding pockets of both proteins plays a role in electrostatic interactions (Arg35 and Arg263 in CHI3L1 and Arg104 and Arg132 in CHIT1) further demonstrating shared evolutionary origin of their sugarbinding capabilities. 56 Building upon these structural insights, we hypothesized that it would be feasible to find small molecule binders of CHI3L1 among our library of potent chitinase inhibitors OATD-01, 57−59 OAT-177, 60,61 OAT-870, 62 OAT-1441, 63 OAT-2068, 64 and their close analogues. To validate this hypothesis, we employed a biophysical technique, microscale thermophoresis, to assess direct binding of approximately 500 compounds from our chitinase inhibitors library to fluorescently labeled CHI3L1 and mCHI3L1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The D138A and E140L mutations in the DXDXE catalytic triad not only deprived CHI3L1 of catalytic abilities but also of the enzyme–substrate electrostatic attraction, which is the key substrate-binding force in chitinases making this part of the pocket of CHI3L1 much more hydrophobic. To better fit the lipophilic pocket of CHI3L1, these fragments need to be much less polar compared to the aminotriazole ring of the most potent CHIT1 inhibitors. A common feature observed in all of the hit compounds 1 – 5 was the presence of a hydrogen bond acceptor (either a nitrogen or oxygen atom) in heterocyclic ring, i.e., 2-thiazolyl, 1-isooxazolyl, 2-pirydyl. Subsequently, we confirmed the specific binding of these compounds to the chitin-binding domain (CBD) of CHI3L1 using X-ray crystallography (compound 1 PDB 8R41 – CHI3L1: 1, compound 2 PDB 8R42 – CH3L1: 2 ; for more details see the experimental part and the Supporting Information) and MicroScale Thermophoresis (MST) displacement assays with chitin hexamer.…”
Section: Resultsmentioning
confidence: 99%
“…Studies based on this model have shown that foxtail millet peptides produced by protein hydrolysis can alleviate DSS-induced colitis in mice by inhibiting NLRP3 inflammatory vesicle formation and Th17 cell differentiation [46]. Acidic Mammalian Chitinase Inhibitor OAT-177 alleviates DSS-induced injury by exerting anti-inflammatory effects [47]. In addition, rice protein peptides can alleviate DSS-induced colitis by modulating intestinal flora and modulating Keap1-Nrf2 [23,48].…”
Section: Discussionmentioning
confidence: 99%
“…CHIT1 expression increases during monocyte-macrophage differentiation (197). Macrophages treated with 2-deoxyglucose exhibit reduced CHIT1 expression (198), revealing a link between the process of glycolysis and CHIT1 induction. CHIT1 is a well-known biomarker in lung sarcoidosis, which correlated with diseases severity and progression (199).…”
Section: Chit1mentioning
confidence: 96%
“…Similarly, OATD-01 suppresses granuloma formation in a murine MWCNT + ESAT6 sarcoidosis model, while modulating immune responses in macrophages ( 134 ). OATD-01 has demonstrated efficacy in multiple models characterized by chronic inflammation and fibrosis including pulmonary fibrosis ( 133 ), non-alcoholic steatohepatitis ( 135 ), inflammatory bowel disease ( 200 ) and chronic asthma ( 201 ) – diseases where pathological macrophages contribute to chronic inflammation leading to fibrotic changes. First-in-human proof-of-concept phase II clinical study assessing efficacy of OATD-01 in patients with pulmonary sarcoidosis will use F-FDG PET/CT imaging as a primary endpoint (study number: NCT06205121).…”
Section: Chit1mentioning
confidence: 99%